PENINGKATAN SKOR DOKKAI PADA UJIAN BERBAHASA JEPANG DENGAN METODE EXTENSIVE READING DI STBA - Adi Novri Yanto; sudjarwo sudjarwo; sumadi sumadi (Program Studi Magister Manajemen Pendidikan)
The objectives of the research are: (1) to conduct learning process in Dokkai (reading) subject through extensive reading ; (2) to find out the increase of students JLPT N3 achievements particularly in reading session; (3) to confirm the effectiveness of extensive reading in Dokkai IV subject at STBA Teknokrat Lampung. Observation and tests were employed in this research to 20 participants in the fifth semester of 2014/2015 academic year. The result of the research shows that (1) the process of teaching learning process through extensive reading was tailored effectively based on the indicator of the attainment of learning objectives. (2) Extensive reading contributes positively in the increase of students score in reading indicated by the increase of JLPT N3 test in each cycle. (3) At the third cycle the standard minimum score of 70 was achieved by 76% of total number of student with average score of 77,14. The findings may suggest that extensive reading can be effectively used by teacher in developing students reading ability.Tujuan penelitian ini adalah (1) Untuk melaksanakan proses pembelajaran mata kuliah Dokkai (membaca) menggunakan pendekatan Extensive Reading; (2) Mengetahui peningkatan skor UKBJ N3 mahasiswa dalam sesi membaca; (3) Membuktikan pendekatan Extensive Reading dapat meningkatkan skor Dokkai UKBJ N3. Penelitian ini merupakan Penelitian Tindakan Kelas menggunakan pendekatanl pembelajaran ASSURE mata kuliah Dokkai IV STBA Teknokrat Lampung. Berdasarkan hasil penelitian diperoleh bahwa (1) Pelaksanaan proses pembelajaran Dokkai dengan model Extensive Reading berjalan dengan baik sesuai dengan kebutuhan belajar, tujuan pembelajaran, materi, metode dan evaluasi; (2) Adanya peningkatan skor sesi Dokkai UKBJ N3; (3) Pendekatan Extensive Reading secara signifikan sangat berperan dalam peningkataan skor Dokkai UKBJ N3 ; dan berdasarkan pada hasil belajar mahasiswa dari siklus I hingga III berada pada predikat tuntas dengan nilai rata-rata hasil belajar mencapai 77,14.Kata Kunci: dokkai (membaca), UKBJ, extensive reading